Korean Rice, Taiwan Rice, and Japanese Agricultural Stagnation: An Economic Consequence of Colonialism - Hayami, Yujiro; Ruttan, V. W. (Quarterly Journal of Economics, 1970)
I. Empirical observation and hypothesis, 564. — Quantitative analysis, 574. — III. Findings and implications, 579.